Mapeamento da economia criativa em Santa Maria (RS) - Assis, Anisme Paim de (2022)
Creative Economy is the set that encompasses the creation, production and distribution of products and services that use creativity as their main productive resource, that is, they are economic activities that combine creativity with techniques and technology, adding value to intellectual assets (JAGER, 2014). This study is dedicated to exploring the Creative Economy in Santa Maria (RS). The objective is to map the Creative Economy initiatives in the county, as well as to identify the economic contributions of creative enterprises to local development. In this sense, a conceptual analysis of the Creative Economy is proposed, based on multiple socioeconomic indicators. Through field research and the analysis of secondary data, we seek to identify the most expressive creative industries in the county and their contributions to local development. In order to respond to the proposed problem and achieve the objectives, exploratory field research was carried out, with the implementation of quantitative and qualitative analysis techniques, in addition to the application of statistical methods to describe the results. It was found that the most representative area in Santa Maria is Culture, with the largest number of creative ventures and employment relationships. It was found that the area of Technology generates higher remuneration for creative workers. The COVID-19 pandemic had a negative effect on participants, impacting their creative ability and consequently their ability to make payments. It was found that the main barriers to the advancement of the Creative Economy are the lack of financing and investments in the public and private spheres. It is inferred that the Creative Economy drives economic and social development in Santa Maria, by boosting the creative sector by overcoming challenges, expanding the creative sharing network and generating tangible and intangible values.